2017
DOI: 10.1007/978-3-319-67208-3_14
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Fraudulent Bank Checks

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…They have also analyzed printed security features on currency notes. Chhabra et al [2] have developed a method for detecting fraudulent bank checks, including checks whose text has been altered using invisible ink. However, this method for alteration detection does not work well for printed documents.…”
Section: Related Workmentioning
confidence: 99%
“…They have also analyzed printed security features on currency notes. Chhabra et al [2] have developed a method for detecting fraudulent bank checks, including checks whose text has been altered using invisible ink. However, this method for alteration detection does not work well for printed documents.…”
Section: Related Workmentioning
confidence: 99%
“…The Cristo Salvador corpus is a 19th century Spanish manuscript provided by Biblioteca Valenciana Digital (Bi-ValDi), and it is publicly available for research purposes on the website of the Pattern Recognition and Human Language Technology (PRHLT) research center 1 . It is a single writer book composed of 53 pages (the page 41 is presented in Figure 3)…”
Section: Historical Manuscript: the Cristo Salvador Corpusmentioning
confidence: 99%
“…Many documents used every day include handwritten text and, in many cases, such as for detecting fraudulent bank checks [1], it would be interesting to recognise these text images automatically. However, state-of-the-art handwritten text recognition (HTR) systems can not suppress the need of human supervision when high quality transcriptions are needed [2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Pradheepan Raghavan and Neamat El Gayar, 2019 reported a general way to perform the fraud detection using machine learning and deep learning. Saheb Chhabra et al, 2017 reported a method used to detect fraudulent bank checks. Abd-ElZaher, 2014 discussed certain inks' affection to physically erased handwriting in fraud checks.…”
Section: Introductionmentioning
confidence: 99%